Պատմողի կերպարը Խաչատուր Աբովեանի «Վէրք Հայաստանի» վէպի կառոյցում - Սողոյեան, Աստղիկ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Нарратор романа «Раны Армении» — не действующая, но выраженная личность. В основном имея черты народного сказителя, он местами несет печать внетекстогого, истинного автора. Голос нарратора предает движение повествованию, а его изменение определяет разнообразие качества текста. У романа орнаментарный сказ, он содержит художественные, исторические, мифические, лирические и философские тексты, в каждом из них слышен голос отдельной личности одного и того же рассказчика. Автор местами, в качестве способа представления, применяет факторы шума и тишины. В «Зангу», например, динамика неистового движения и статика спокойной тишины развиваются в гармонии ночи и дня. The narrator of the novel “Wounds of Armenia” is not an active, but a pronounced personality. Basically, having the features of a folk storyteller, in some places he bears the stamp of a non-textual, true author. The voice of the narrator imparts movement to the narrative, and its change determines the diversity of the quality of the text. The novel has an ornamental character, it contains artistic, historical, mythical, lyrical and philosophical components; in each of them the voice of a separate personality of the same narrator is heard. The author in some places, as a method of presentation, uses the factors of noise and silence. In “Zangu”, for instance, the dynamics of the frantic movement and the statics of peaceful silence develop in the harmony of the day and night.
Keywords: Պատմութիւն; Բանասիրութիւն